PENGARUH STRATEGI PAIKEM BERBANTUAN ALAT PERAGA PAPIKDIG TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV - Wahyuni, Sri; Buyung; Safrihady (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
This study aims to determine the effect of the PAIKEM strategy with the 'Papikdig' teaching aid and to determine whether or not there is an effect of the PAIKEM strategy with the 'Papikdig' teaching aid on students' interest and mathematics learning outcomes. The research method is Quasi Experiment with Posttest-Only Control Group Design. The research sample uses non-probability sampling techniques. The results of the study: the Ho hypothesis is rejected and the Ha hypothesis is accepted at a significance level of 0.05. The prerequisite tests carried out are normality, homogeneity, and linearity tests using SPSS version 27. The hypothesis was tested using an independent sample t-test. The study shows that there is an effect of the PAIKEM strategy with the 'Papikdig' teaching aid on students' interest and mathematics learning outcomes. This is indicated by an independent t-test of 0.001 which is smaller than 0.05. The positive impact of the PAIKEM strategy with the 'Papikdig' teaching aid on students' interest and mathematics learning outcomes. This is indicated by the average student interest in learning at a score of 83.02 for the very high category. And the average student learning outcomes are at a score of 66.5 with a sufficient category.